Medical Errors and Patient Safety: A Curriculum Guide for Teaching Medical Students and Family Practice Residents - Joseph Halbach; Laurie Sullivan (Association of American Medical Colleges, 2005)
Abstract This resource is a curriculum guide designed to teach medical students and family practice residents about medical errors and patient safety-a glaring deficit in medical education. Now in its third edition, this guide originally grew out of our own teaching of medical errors and patient safety to third-year medical students and family practice residents. Nine chapters provide a thorough review of the literature in this area and include: (1) Introduction, Background, Epidemiology, and History; (2) Ethical, Legal, Professional Issues and the Culture of Medicine; (3) Recommended Management of Medical Errors Part I: Overview; (4) Recommended Management of Medical Errors Part II: Disclosure; (5) Effects of Making an Error on the Physician and the Importance of Personal Awareness; (6) Prevention of Medical Errors Part I: Overview; (7) Prevention of Medical Errors Part II: Medication Errors; (8) Education of Medical Students and Residents About Patient Safety and Medical Error Part I: The Literature; and (9) Education of Medical Students and Residents About Patient Safety and Medical Error Part II: Curriculum Resources.